Lubricating aluminum sheet with high heat dissipation performance and preparation method thereof

By uniformly applying functional coatings on the surface of the aluminum sheet to form high-heat dissipation lubricating aluminum sheets, the problem of insufficient heat dissipation and lubricity in the drilling process of PCB boards is solved, and more efficient heat dissipation and lubrication are achieved, improving the quality and service life of the drilling holes.

CN119875453AActive Publication Date: 2025-04-25GUANGDONG HEZHENG TECH CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510056603.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

During the drilling process of PCB board, the existing coated aluminum sheets are insufficient in heat dissipation and lubricity, resulting in excessive temperature of the drilling needle and damage to friction, which affects the drilling quality and hole position accuracy. At the same time, the coating is prone to fall off, reducing service life.

Method used

Functional coating is used to uniformly coat the surface of the aluminum sheet to form a high heat dissipation lubricating aluminum sheet. Functional coatings consist of polyacrylate, boron nitride nanosheets, cellulose hydrogel, polyethyleneimine, modified sodium alginate and polyether modified organosiloxane, with excellent adhesion and thermal conductivity.

Benefits of technology

It improves the heat dissipation effect and lubrication performance during the drilling process, reduces the friction and wear of the drilling needle, extends the service life of the drilling needle, reduces the drilling hole roughness, and improves the hole position accuracy and drilling quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005241613870000091
    Figure BDA0005241613870000091
Patent Text Reader

Abstract

The invention relates to the technical field of heat dissipation lubricating aluminum sheets, and discloses a high-heat dissipation lubricating aluminum sheet and a preparation method thereof. The high-heat-dissipation lubricating aluminum sheet is prepared by uniformly coating the surface of an aluminum sheet with a functional coating, and the functional coating is prepared from the following raw materials in parts by weight: 45-55 parts of polyacrylate, 6-10 parts of boron nitride nanosheets, 12-18 parts of cellulose hydrogel, 3-6 parts of polyethyleneimine, 5-10 parts of modified sodium alginate and 0.2-0.5 part of a flatting agent, the functional coating has excellent adhesive force and thermal conductivity, can quickly disperse heat of a drill point during drilling without cracking, also has lubricity, and can reduce friction and wear of the drill point, prolong the service life of the drill point, reduce the roughness of a drilled hole and improve the quality of the drilled hole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat dissipation lubricating aluminum sheets, and in particular to a lubricating aluminum sheet with high heat dissipation performance and a preparation method thereof. Background Art

[0002] With the rapid development of electronic equipment, computers, smart cars and other fields, PCB boards, as one of the key parts, are receiving more and more attention. In recent years, circuit board design and manufacturing have gradually tended to be multi-layered, laminated, functionalized, integrated, light, thin, short and small, and PCB drilling technology has also been continuously improving. Among them, micro-hole, high-precision, high-quality and diversified development of PCB board drilling technology is the current main trend.

[0003] During the drilling process of PCB boards, cover plates (aluminum sheets, coated aluminum sheets, etc.) are generally used to protect the PCB board and improve the drilling quality. Compared with ordinary aluminum sheets, coated aluminum sheets can use the synergistic effect of the coating on the surface of the aluminum sheet and the aluminum sheet to improve the drilling quality. At present, the coating on the surface of the aluminum sheet is a viscous resin. These resins have poor heat dissipation and lubricity. The coating cannot effectively dissipate the heat generated by the drill needle and cannot reduce the friction between the drill needle and the workpiece. This causes the drill needle to affect the drilling quality and hole position accuracy due to excessive temperature and friction damage. In addition, since the surface of the aluminum sheet is relatively smooth, the resin with average adhesion will cause the coating to fall off the surface of the aluminum sheet after long-term use, which greatly reduces the service life of the coated aluminum sheet. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a lubricating aluminum sheet with high heat dissipation and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high heat dissipation lubricating aluminum sheet, comprising a functional coating and an aluminum sheet; the functional coating is formed by uniformly coating the functional coating on the surface of the aluminum sheet;

[0007] The functional coating comprises the following raw materials in parts by weight: 45-55 parts of polyacrylate, 6-10 parts of boron nitride nanosheets, 12-18 parts of cellulose hydrogel, 3-6 parts of polyethyleneimine, 5-10 parts of modified sodium alginate, and 0.2-0.5 parts of leveling agent;

[0008] The leveling agent is polyether-modified organic siloxane;

[0009] The cellulose hydrogel is prepared by the following steps:

[0010] Step A1, mixing nano calcium carbonate, ethanol and sodium dodecyl sulfate and stirring evenly, then adding KH-570 (silane coupling agent) and deionized water and stirring for 24 hours, centrifuging, washing, drying, and collecting the precipitate; then stirring sodium dodecyl sulfate and sodium bicarbonate in deionized water for 30-60 minutes, then adding n-hexadecane, precipitate, acrylic acid and azobisisobutyronitrile and stirring evenly, ultrasonically treating in an ice water bath for 10 minutes, heating to 60-80° C. under nitrogen conditions, stirring and reacting for 3-5 hours, and obtaining modified calcium carbonate;

[0011] Further, in the precipitation of step A1, the dosage ratio of nano calcium carbonate, ethanol, sodium dodecyl sulfate, KH-570 and deionized water is 5 g: 40 mL: 0.02-0.05 g: 0.5-1.5 mL: 10 mL;

[0012] Further, in step A1, the amount ratio of sodium dodecyl sulfate, sodium bicarbonate, deionized water, n-hexadecane, precipitate, acrylic acid and azobisisobutyronitrile in the modified calcium carbonate is 0.01-0.03 g: 0.005-0.01 g: 20 mL: 0.5-1 mL: 3-5 g: 2-4 g: 0.002-0.005 g;

[0013] Step A2, mixing sodium dodecyl sulfate, sodium chloride and deionized water, stirring evenly, adding modified cellulose and modified calcium carbonate, stirring for 1.5-2.5 hours, adding potassium persulfate and N,N,N',N'-tetramethylethylenediamine, stirring for 20-30 minutes, ultrasonically treating for 5-10 minutes, and then heating to 40-50° C. and standing for 5-8 hours to obtain cellulose hydrogel;

[0014] Further, in step A2, the dosage ratio of sodium dodecyl sulfate, sodium chloride, deionized water, modified cellulose, modified calcium carbonate, potassium persulfate and N,N,N',N'-tetramethylethylenediamine is 0.5-1.5 g: 0.3-0.9 g: 20-60 mL: 6-10 g: 0.1-0.2 g: 0.012-0.02 g: 0.0001 g;

[0015] Furthermore, the modified cellulose in step A2 is prepared by the following steps: dispersing the nanocellulose evenly in N,N-dimethylformamide, adding 6-bromo-1-hexene and sodium hydroxide, heating to 30-40° C., stirring and reacting for 18-24 hours, centrifuging, and purifying to obtain the modified cellulose;

[0016] Furthermore, the dosage ratio of nanocellulose, N,N-dimethylformamide, 6-bromo-1-hexene and sodium hydroxide in the modified cellulose is 2-3 g: 100 mL: 3-5 g: 1.5-3 g.

[0017] The modified sodium alginate is prepared by the following steps:

[0018] Step B1, add sodium alginate to deionized water, stir evenly in a 45°C water bath, then add EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and NHS (N-hydroxysuccinimide) and stir for 2-3 hours, then add dopamine hydrochloride, stir and react for 8-12 hours, let stand for 24 hours, filter and dry to obtain modified sodium alginate;

[0019] Furthermore, in step B1, the usage ratio of sodium alginate, deionized water, EDC, NHS and dopamine hydrochloride is 5-10 g:100 mL:1.25-2.5 g:1-2 g:2-4 g.

[0020] A method for preparing a lubricating aluminum sheet with high heat dissipation performance comprises the following steps:

[0021] Step S1, weighing raw materials by weight, adding polyacrylate, boron nitride nanosheets, cellulose hydrogel, polyethyleneimine, modified sodium alginate and leveling agent into a stirrer and stirring evenly to obtain a functional coating;

[0022] Step S2, coating the functional coating evenly on the aluminum sheet to form a coating with a thickness of 0.2 mm, and drying the coating to obtain a lubricating aluminum sheet with high heat dissipation.

[0023] Beneficial effects of the present invention:

[0024] The high heat dissipation lubricating aluminum sheet in the present invention is prepared by uniformly coating the surface of the aluminum sheet with a functional coating. The functional coating has excellent adhesion and thermal conductivity, can quickly disperse the heat of the drill bit during drilling without cracking, and also has lubricity, can reduce the friction and wear of the drill bit, increase the service life of the drill bit, reduce the roughness of the drill hole, and improve the quality of the drill hole.

[0025] The functional coating in the present invention plays the role of heat dissipation on the surface of the aluminum sheet, lubricating the drill bit, reducing the temperature of the drill bit, and improving the quality of the drill hole wall; the cellulose hydrogel introduced in the functional coating first uses KH-570 to perform surface treatment on calcium carbonate to obtain a precipitate containing a double bond structure, and then uses acrylic acid as a raw material and azobisisobutyronitrile as an initiator to synthesize polyacrylic acid on the surface of the precipitate to obtain modified calcium carbonate; then uses 6-bromo-1-hexene to modify the cellulose, and finally uses the double bonds introduced in the modified cellulose and the modified calcium carbonate to perform free radical polymerization to synthesize the cellulose hydrogel.

[0026] Cellulose hydrogel significantly improves the lubricity of the coating, because the hydrogel can form a lubricating film between the drill and the drill, effectively reducing the friction coefficient. At the same time, the hydrogel can also continuously replenish the moisture of the lubricating layer during the friction process through its water absorption and water retention capabilities, ensuring the durability of the lubrication effect, thereby reducing the friction and wear of the drill, increasing the service life of the drill, reducing the frequency of replacing the drill, and reducing production costs. In addition, the modified calcium carbonate contained in the hydrogel is evenly distributed in the hydrogel network to form new cross-linking points, which can enhance the mechanical properties of the hydrogel and thus enhance the mechanical properties of the coating, reduce the vibration and shaking of the drill during the drilling process, and thus reduce the occurrence of drill breakage and other phenomena. At the same time, the hydrogel also acts as an adhesive in the matrix, which can absorb the moisture in the matrix to form adhesion, enhance the bonding force between the coating and the aluminum sheet substrate, and improve the durability and service life of the coating.

[0027] The modified sodium alginate introduced in the functional coating is prepared by reacting sodium alginate with dopamine hydrochloride. The catechol structure introduced in the modified sodium alginate can interact with the hydroxyl groups on the surface of the aluminum sheet through hydrogen bonding, thereby achieving intermolecular adhesion, improving the adhesion between the functional coating and the aluminum sheet substrate, reducing cracking and shedding of the coating during drilling, and increasing the service life of the aluminum sheet; in addition, sodium alginate itself has a three-dimensional network structure, which can synergize with high molecular polymers such as polyacrylate after the coating is formed, play a supporting role inside the coating, and can stabilize the drill bit when drilling, reduce deflection, and improve hole position accuracy. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1: Modified cellulose was prepared by the following steps: 2 g of nanocellulose was evenly dispersed in 100 mL of N,N-dimethylformamide, 3 g of 6-bromo-1-hexene and 1.5 g of sodium hydroxide were added, and the temperature was raised to 30° C. and stirred for reaction for 18 h, followed by centrifugation and purification to obtain modified cellulose.

[0030] The cellulose hydrogel was prepared by the following steps:

[0031] Step A1, 5g of nano calcium carbonate, 40mL of ethanol and 0.02g of sodium dodecyl sulfate were mixed and stirred evenly, and then 0.5mL of KH-570 and 10mL of deionized water were added and stirred for 24h, centrifuged, washed, dried, and the precipitate was collected; then 0.01g of sodium dodecyl sulfate and 0.005g of sodium bicarbonate were stirred in 20mL of deionized water for 30min, and then 0.5mL of n-hexadecane, 3g of precipitate, 2g of acrylic acid and 0.002g of azobisisobutyronitrile were added and stirred evenly, and ultrasonic treatment was carried out in an ice water bath for 10min, and heated to 60°C under nitrogen conditions, and stirred for reaction for 3h to obtain modified calcium carbonate;

[0032] Step A2, 0.5 g of sodium dodecyl sulfate, 0.3 g of sodium chloride and 20 mL of deionized water were mixed and stirred evenly, and then 6 g of modified cellulose and 0.1 g of modified calcium carbonate were added, and stirred for 1.5 h, and then 0.012 g of potassium persulfate and 0.0001 g of N,N,N',N'-tetramethylethylenediamine were added and stirred for 20 min, and then ultrasonically treated for 5 min, and then heated to 40 ° C and allowed to stand for 5 h to obtain cellulose hydrogel.

[0033] Modified sodium alginate is prepared by the following steps:

[0034] Add 5 g of sodium alginate into 100 mL of deionized water and stir evenly in a 45°C water bath. Then add 1.25 g of EDC and 1 g of NHS and stir for 2 h. Then add 2 g of dopamine hydrochloride and stir for 8 h. Let stand for 24 h, filter and dry to obtain modified sodium alginate.

[0035] Example 2: Modified cellulose was prepared by the following steps: 2.5 g of nanocellulose was evenly dispersed in 100 mL of N,N-dimethylformamide, 4 g of 6-bromo-1-hexene and 2.2 g of sodium hydroxide were added, and the mixture was heated to 35° C. and stirred for 21 h, centrifuged, and purified to obtain modified cellulose.

[0036] The cellulose hydrogel was prepared by the following steps:

[0037] Step A1, 5g of nano calcium carbonate, 40mL of ethanol and 0.035g of sodium dodecyl sulfate were mixed and stirred evenly, and then 1mL of KH-570 and 10mL of deionized water were added and stirred for 24h, centrifuged, washed, dried, and the precipitate was collected; then 0.02g of sodium dodecyl sulfate and 0.0075g of sodium bicarbonate were stirred in 20mL of deionized water for 45min, and then 0.75mL of n-hexadecane, 4g of precipitate, 3g of acrylic acid and 0.0035g of azobisisobutyronitrile were added and stirred evenly, and ultrasonic treatment was carried out in an ice water bath for 10min, and heated to 70°C under nitrogen conditions, and stirred for reaction for 4h to obtain modified calcium carbonate;

[0038] Step A2, 1 g of sodium dodecyl sulfate, 0.6 g of sodium chloride and 40 mL of deionized water were mixed and stirred evenly, and then 8 g of modified cellulose and 0.15 g of modified calcium carbonate were added, and stirred for 2 h. Then, 0.016 g of potassium persulfate and 0.0001 g of N,N,N',N'-tetramethylethylenediamine were added, and stirred for 25 min. Then, ultrasonic treatment was performed for 8 min, and then the temperature was raised to 45 ° C and allowed to stand for 6.5 h to obtain cellulose hydrogel.

[0039] Modified sodium alginate is prepared by the following steps:

[0040] Add 7.5 g of sodium alginate into 100 mL of deionized water and stir evenly in a 45°C water bath. Then add 1.9 g of EDC and 1.5 g of NHS and stir for 2.5 h. Then add 3 g of dopamine hydrochloride and stir to react for 10 h. Let stand for 24 h, filter and dry to obtain modified sodium alginate.

[0041] Example 3: Modified cellulose was prepared by the following steps: 3 g of nanocellulose was evenly dispersed in 100 mL of N,N-dimethylformamide, 5 g of 6-bromo-1-hexene and 3 g of sodium hydroxide were added, and the temperature was raised to 40° C. and stirred for reaction for 24 h, centrifuged, and purified to obtain modified cellulose.

[0042] The cellulose hydrogel was prepared by the following steps:

[0043] Step A1, 5g of nano calcium carbonate, 40mL of ethanol and 0.05g of sodium dodecyl sulfate were mixed and stirred evenly, and then 1.5mL of KH-570 and 10mL of deionized water were added and stirred for 24h, centrifuged, washed, dried, and the precipitate was collected; then 0.03g of sodium dodecyl sulfate and 0.01g of sodium bicarbonate were stirred in 20mL of deionized water for 60min, and then 1mL of n-hexadecane, 5g of precipitate, 4g of acrylic acid and 0.005g of azobisisobutyronitrile were added and stirred evenly, and ultrasonic treatment was carried out in an ice water bath for 10min, and heated to 80°C under nitrogen conditions, and stirred for reaction for 5h to obtain modified calcium carbonate;

[0044] Step A2, 1.5 g of sodium dodecyl sulfate, 0.9 g of sodium chloride and 60 mL of deionized water were mixed and stirred evenly, and then 10 g of modified cellulose and 0.2 g of modified calcium carbonate were added, and stirred for 2.5 h, and then 0.02 g of potassium persulfate and 0.0001 g of N,N,N',N'-tetramethylethylenediamine were added and stirred for 30 min, and then ultrasonically treated for 10 min, and then heated to 50 ° C and allowed to stand for 8 h to obtain cellulose hydrogel.

[0045] Modified sodium alginate is prepared by the following steps:

[0046] Add 10 g of sodium alginate into 100 mL of deionized water and stir evenly in a 45°C water bath. Then add 2.5 g of EDC and 2 g of NHS and stir for 3 h. Then add 4 g of dopamine hydrochloride and stir for 12 h. Let stand for 24 h, filter and dry to obtain modified sodium alginate.

[0047] Embodiment 4: A method for preparing a lubricating aluminum sheet with high heat dissipation performance comprises the following steps:

[0048] 45 parts of polyacrylate, 6 parts of boron nitride nanosheets, 12 parts of cellulose hydrogel prepared in Example 1, 3 parts of polyethyleneimine, 5 parts of modified sodium alginate prepared in Example 1, and 0.2 parts of polyether-modified organosiloxane;

[0049] Step S1, weighing raw materials by weight, adding polyacrylate, boron nitride nanosheets, cellulose hydrogel prepared in Example 1, polyethyleneimine, modified sodium alginate prepared in Example 1 and polyether-modified organosiloxane into a stirrer and stirring evenly to obtain a functional coating;

[0050] Step S2, coating the functional coating evenly on the aluminum sheet to form a coating with a thickness of 0.2 mm, and drying the coating to obtain a lubricating aluminum sheet with high heat dissipation.

[0051] Embodiment 5: A method for preparing a lubricating aluminum sheet with high heat dissipation performance comprises the following steps:

[0052] 50 parts of polyacrylate, 8 parts of boron nitride nanosheets, 15 parts of cellulose hydrogel prepared in Example 2, 4.5 parts of polyethyleneimine, 7.5 parts of modified sodium alginate prepared in Example 2, and 0.3 parts of polyether-modified organosiloxane;

[0053] Step S1, weighing raw materials by weight, adding polyacrylate, boron nitride nanosheets, cellulose hydrogel prepared in Example 2, polyethyleneimine, modified sodium alginate prepared in Example 2 and polyether-modified organosiloxane into a stirrer and stirring evenly to obtain a functional coating;

[0054] Step S2, coating the functional coating evenly on the aluminum sheet to form a coating with a thickness of 0.2 mm, and drying the coating to obtain a lubricating aluminum sheet with high heat dissipation.

[0055] Embodiment 6: A method for preparing a lubricating aluminum sheet with high heat dissipation performance comprises the following steps:

[0056] 55 parts of polyacrylate, 10 parts of boron nitride nanosheets, 18 parts of cellulose hydrogel prepared in Example 3, 6 parts of polyethyleneimine, 10 parts of modified sodium alginate prepared in Example 3, and 0.5 parts of polyether-modified organosiloxane;

[0057] Step S1, weighing raw materials by weight, adding polyacrylate, boron nitride nanosheets, cellulose hydrogel prepared in Example 3, polyethyleneimine, modified sodium alginate prepared in Example 3 and polyether-modified organosiloxane into a stirrer and stirring evenly to obtain a functional coating;

[0058] Step S2, coating the functional coating evenly on the aluminum sheet to form a coating with a thickness of 0.2 mm, and drying the coating to obtain a lubricating aluminum sheet with high heat dissipation.

[0059] Comparative Example 1: This comparative example is a lubricating aluminum sheet. The difference from Example 6 is that the cellulose hydrogel prepared in Example 3 is replaced by commercially available cellulose hydrogel, and the rest is the same.

[0060] Comparative Example 2: This comparative example is a lubricating aluminum sheet. The difference from Example 6 is that sodium alginate is used instead of the modified sodium alginate prepared in Example 3, and the rest is the same.

[0061] The lubricating aluminum sheets prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:

[0062] Adhesion test: Use a grid cutter to draw 10×10 1mm squares on the coating film, stick 3M special transparent tape on the grid area, pull it 180° quickly, and observe whether there is any coating peeling off on the lubricating aluminum sheet; it is divided into 0 to 5 levels according to the peeling situation, with no peeling phenomenon as the best level 0, peeling with a peeling area of ​​less than 10% as level 1, shedding of not less than 10% and less than 30% as level 2, shedding area of ​​not less than 30% and less than 50% as level 3, shedding area of ​​not less than 50% and less than 70% as level 4, and shedding area of ​​not less than 70% as level 5;

[0063] Drilling test: The lubricated aluminum sheet sample was drilled with a hole diameter of 0.25 mm to test the hole wall roughness and hole position accuracy;

[0064] Thermal conductivity test: According to ASTM E1530 coating thermal conductivity test standard test;

[0065] The test results are shown in Table 1:

[0066] Table 1: Performance test results

[0067]

[0068] It can be seen from Table 1 that the functional coating of the present invention has excellent adhesion and heat dissipation performance on the surface of the aluminum sheet. When the aluminum sheet is used for drilling holes in a PCB board, it can effectively improve the hole wall quality and hole position accuracy when drilling holes in the PCB board, while avoiding the breakage of the drill needle during the drilling process and reducing costs.

[0069] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A lubricating aluminum sheet with high heat dissipation, characterized in that: It comprises a functional coating and an aluminum sheet; the functional coating is formed by uniformly coating the functional coating on the surface of the aluminum sheet; The functional coating comprises the following raw materials in parts by weight: 45-55 parts of polyacrylate, 6-10 parts of boron nitride nanosheets, 12-18 parts of cellulose hydrogel, 3-6 parts of polyethyleneimine, 5-10 parts of modified sodium alginate, and 0.2-0.5 parts of leveling agent; The cellulose hydrogel is prepared by the following steps: Step A1, mixing nano calcium carbonate, ethanol and sodium dodecyl sulfate, stirring evenly, then adding KH-570 and deionized water and stirring for 24 hours, centrifuging, washing, drying, and collecting the precipitate; then stirring sodium dodecyl sulfate and sodium bicarbonate in deionized water for 30-60 minutes, then adding n-hexadecane, precipitate, acrylic acid and azobisisobutyronitrile and stirring evenly, ultrasonically treating in an ice water bath for 10 minutes, heating to 60-80° C. under nitrogen conditions, stirring and reacting for 3-5 hours, and obtaining modified calcium carbonate; Step A2, mix sodium dodecyl sulfate, sodium chloride and deionized water and stir evenly, then add modified cellulose and modified calcium carbonate, stir for 1.5-2.5h, then add potassium persulfate and N,N,N',N'-tetramethylethylenediamine, stir for 20-30min, then ultrasonically treat for 5-10min, then heat to 40-50°C and stand for 5-8h to obtain cellulose hydrogel.

2. The high heat dissipation lubricating aluminum sheet according to claim 1, characterized in that: In step A1, the dosage ratio of nano calcium carbonate, ethanol, sodium dodecyl sulfate, KH-570 and deionized water in the precipitation is 5 g:40 mL:0.02-0.05 g:0.5-1.5 mL:10 mL.

3. The high heat dissipation lubricating aluminum sheet according to claim 1, characterized in that: Step A1: The dosage ratio of sodium dodecyl sulfate, sodium bicarbonate, deionized water, n-hexadecane, precipitate, acrylic acid and azobisisobutyronitrile in the modified calcium carbonate is 0.01-0.03 g: 0.005-0.01 g: 20 mL: 0.5-1 mL: 3-5 g: 2-4 g: 0.002-0.005 g.

4. The high heat dissipation lubricating aluminum sheet according to claim 1, characterized in that: In step A2, the usage ratio of sodium dodecyl sulfate, sodium chloride, deionized water, modified cellulose, modified calcium carbonate, potassium persulfate and N,N,N',N'-tetramethylethylenediamine is 0.5-1.5g: 0.3-0.9g: 20-60mL: 6-10g: 0.1-0.2g: 0.012-0.02g: 0.0001g.

5. The high heat dissipation lubricating aluminum sheet according to claim 1, characterized in that: The modified cellulose in step A2 is prepared by the following steps: nanocellulose is evenly dispersed in N,N-dimethylformamide, 6-bromo-1-hexene and sodium hydroxide are added, and the temperature is raised to 30-40° C. and stirred for reaction for 18-24 hours, centrifuged, and purified to obtain modified cellulose.

6. The high heat dissipation lubricating aluminum sheet according to claim 5, characterized in that: The dosage ratio of nanocellulose, N,N-dimethylformamide, 6-bromo-1-hexene and sodium hydroxide in the modified cellulose is 2-3g:100mL:3-5g:1.5-3g.

7. The high heat dissipation lubricating aluminum sheet according to claim 1, characterized in that: The modified sodium alginate is prepared by the following steps: Add 5-10g sodium alginate to 100mL deionized water and stir evenly in a 45°C water bath. Then add 1.25-2.5g EDC and 1-2g NHS and stir for 2-3h. Then add 2-4g dopamine hydrochloride and stir for 8-12h. Let stand for 24h, filter and dry to obtain modified sodium alginate.

8. The high heat dissipation lubricating aluminum sheet according to claim 7, characterized in that: The dosage ratio of sodium alginate, deionized water, EDC, NHS and dopamine hydrochloride in the modified sodium alginate is 5-10 g: 100 mL: 1.25-2.5 g: 1-2 g: 2-4 g.

9. A method for preparing the lubricating aluminum sheet with high heat dissipation performance according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, adding polyacrylate, boron nitride nanosheets, cellulose hydrogel, polyethyleneimine, modified sodium alginate and leveling agent into a stirrer and stirring evenly to obtain a functional coating; Step S2, coating the functional coating evenly on the aluminum sheet to form a coating with a thickness of 0.2 mm, and drying the coating to obtain a lubricating aluminum sheet with high heat dissipation.

Citation Information

Patent Citations

  • Composition with lubrication and heat conduction effects and manufacturing method thereof

    CN103773204A

  • Resin composition, and copper coil substrate and printed circuit board thereof

    CN104583309A

  • Crosslinked modified sodium alginate and preparation method thereof

    CN105330875A

  • Automotive engine cover plate metal surface treatment agent and preparation method thereof

    CN107083188A

  • Heat radiation paint for computer case and preparation method thereof

    CN108329736A